PLANNING TRAINING FOR FOOTBALL PLAYERS AND ORGANIZING TRAINING WORK (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article focuses on planning and organizing the training activities of football players, the comprehensive development of their physical abilities, improving the qualities of strength, speed, endurance, agility, physical qualities, as well as improving their technique and tactics.